O 1.8 cineol inibe a motilidade gastrintestinal em ratos acordados e anestesiados - Neves, José Ricardo Cunha (2006)
It was studied the effect of EOCN and 1,8 cineol, components of the Croton nepetaefolius - plant of North-East of Brasil, used in the popular medicine for riots of the gastrointestinal sistem - on the motor behavior of the gut of Wistar rats. We used 121 male animals, weighing 200-350g, distributed in the two following groups of study: effect of the OECN and the 1,8 cineol on: i) the gastric empyting (GE), the gastrointestinal (GI) transit of liquid and the arterial pressure (AP) in awake rats and ii) the gastric compliance, the AP, the central venous pressure (CVP) and the cardiac frequency (FC) of anaesthetized rats. It was evaluated, in 106 awake rats under starvation for 24h with free access to water, the effect of injection (0,2mL; i.v.) of OECN (3 µg/Kg) or 1,8 cineol (1, 3, 10 and 30 µg/Kg) or vehicle (saline 0.9%) on GE and GI transit of liquid, as well as on AP. A test meal (1,5mL of phenol red - 0,5mg/mL in glucose 5%) was injected in the stomach by gavagem. After 10min,it was sacrificed the animals and obstruct the pyloro, cardia and terminal íleo. It was removed and divide the gut in: stomach and consecutive segments of small intestine (40% proximal; medial 30% and 30% distal). After homogenization of these visceral portions, it was determined the absorbance of the samples at 560nm. The fracional dye retention in each segment allowed the calculation of the GE and GI transit. In a separate group of animals, the AP was monitored continuously by digital system of acquisition data during 20min before and 30min after the treatment with 1.8 cineol or diluente. Treatment with 1,8 cineol (3 µg/Kg) was evaluated also in animals after sacrifice 20 or 30min after gavagem. Compared with control, the gastric retention increase (p<0,05) of 43,9±34% for 54,9±4,7; 61,3±3,3; 56,2±1,7 and 55.8±2.1% in the treated (1.8 cineol 1, 3, 10 and 30 µg/Kg, respectively) animals, sacrificed 10 min after gavage.It was also observed significant reduction on the GI transit in this group. The 1,8 cineol (1, 3, 10 and 30 µg/Kg) induced reduction (p<0,05) of the AP (of 124±5,2 for 119±5,2; 100,2±4,3; 99,8±0,5 and 88,6±2,7mmHg, respectivelly). This effect was, however, fugaz, for dose 1 and 3 µg/Kg, however the doses of 10 and 30 µg/Kg, the animals had not presented recovery of the AP. Treatment with EOCN also increases gastric retention (53,1±2,4 versus 43,9±3,4, p<0,05) while reduces GI transit. The surgical pre-treatment by sub-diafragmatic vagotomy, but not it splancnotomy, inhibited the 1,8 cineol effect on the GE and GI transit of liquid. ii) The effect of 1.8 cineol (1 or 3 µg/Kg) on gastric compliance had been lead in 15 anaesthetized rats, under jejun of 24h. The variations of the gastric volume (GV), had been measured by plethysmography, while the AP, FC and CVP had been monitored continuously by a digital system of data acquisition. We observe reduction of the GV (p<0.05), which was significant on 30, 40, 50 and 60min after treatment (2,0±0,1; 1,9±0,1; 1,8±0,1 and 1,7±0,1mL, versus 2,1±0,2mL) 1 or 3µg/Kg of 1.8 cineole. The AP presented significant fall after the administration of 1.8 cineol, remaining thus during 60min of monitorization (87,9±7,7; 87,6±7,1; 87,9±6,4; 87,8±5,7; 86,0±5,5 and 87,7±6,0mmHg, respectively versus 94,4±6,2; mmHg), as well as the FC (366,3±13,4; 361,7±11,5; 357,3±10,4; 353,0±10,4; 348,3±11,1 and 350,4±13,7bpm, respectively versus 395,2±11,1bpm). The CVP did not suffer significant variations after treatment. In summary, it was observed the OECN and the 1,8 cineol treatments diminish the gut motility, delaying the GE and GI transit of liquid in awake rats; it reduces the gastric complaciance in anaesthetized rats besides presenting effect hipotensor and bradicardic; probably for direct action on the gastrointestinal and vascular smooth muscel and moduling the parassimpatic nervous system